Serological markers of exocrine pancreatic function are differentially informative for distinguishing individuals progressing to type 1 diabetes - Desmond Schatz; Laura Jacobsen; Todd M Brusko; Michael J Haller; Mark Atkinson; MacKenzie D Williams; Catherine Ramsey Grace; Amanda L Posgai; Kieran M McGrail; Maigan A Brusko; Rhonda Bacher; Clive H Wasserfall (BMJ Open Diabetes Research & Care)
Introduction Altered serum levels of growth hormones, adipokines, and exocrine pancreas enzymes have been individually linked with type 1 diabetes (T1D). We collectively evaluated seven such biomarkers, combined with islet autoantibodies (AAb) and genetic risk score (GRS2), for their utility in predicting AAb/T1D status.Research design and methods Cross-sectional serum samples (n=154 T1D, n=56 1AAb+, n=77 ≥2AAb+, n=256 AAb−) were assessed for IGF1, IGF2, adiponectin, leptin, amylase, lipase, and trypsinogen (n=543, age range 2.7–30.0 years) using random forest modeling.Results GRS2, age, lipase, trypsinogen, and AAb against ZnT8, GAD65, and insulin were the most informative markers. Notably, these variables were differentially informative according to AAb/T1D status. Higher GRS2 (p<0.001) and lower lipase levels (p=0.002) favored ≥2AAb+ versus AAb− classification. AAb against ZnT8 (p<0.01), GAD65 (p=0.021), or insulin (p=0.01) each independently favored ≥2AAb+ versus 1AAb+ classification. Reduced trypsinogen (p<0.001) and increased lipase levels (p<0.001) favored recent-onset T1D versus ≥2AAb+ classification.Conclusions Among the serological markers tested, lipase and trypsinogen levels were the most informative for differentiating among clinical groups, with the utility of each enzyme varying according to GRS2 and AAb/T1D status. These data support exocrine pancreas enzymes as candidates for longitudinal follow-up.